Skill Training in Counselling and Psychotherapy - Ellis, Albert (Canadian Journal of Counselling and Psychotherapy, 2012)
Although Rational Emotive Therapy (RET) pioneered in some aspects of skill training, it recognizes some distinct disadvantages in making that approach the modus operandi of counselling. Both the advantages and disadvantages of a skill-training approach are discussed in order to clarify RETs position on the topic.